Granulomatosis with polyangiitis: potentially lethal gingival lesions presenting to the dentist. Issue 4 (24th April 2019) - Patrick, Amy; Altman, Keith
Abstract : Gingival pathology is a daily presentation, however a small number of systemic conditions can manifest similar to a common gingival condition and have fatal results. Dentist referred 56-year-old woman to Oral and Maxillofacial Surgery department with a 2-week medical history of gingival bleeding not responding to local measures. Biopsy showed eosinophilic infiltrate and vasculitis, and blood tests showed positive markers including cytoplasmic antineutrophil cytoplasmatic antibodies. Granulomatosis with polyangiitis is a rare disease affecting the respiratory tract, blood vessels and kidneys. Oral lesions are rarely the primary presenting feature. When left untreated, most cases are fatal within a year of diagnosis. The diagnosis can only be made when certain criteria are found, including granular oral lesions exhibiting an eosinophilic inflammatory infiltrate on biopsy. With 5% of cases showing intraoral lesions as the primary feature, it is essential that dentists have the knowledge of this rare disease to refer and not to treat as a common gingival condition.